The contribution of a critical realist approach to understanding the symptoms and causal explanations of postnatal depression in Malaysia - Mohd Arifin, Siti Roshaidai; cheyne, helen; maxwell, margaret (International Institute for Qualitative Methodology/ Sage Publications, 2016)
Postnatal depression (PND) is considered to be a serious mental health problem for many women worldwide; contributing to increased maternal morbidity and mortality. Although it has been found to be associated with hormonal and sociocultural factors; it remains unclear why the experience of PND varies by context and culture. The aim of this presentation is to evaluate the contribution of critical realism in understanding the symptoms and the perceived causes of PND among women from three different cultural backgrounds. A total of 33 women from three different cultural backgrounds attending for care in six purposively selected Maternal and Child Health clinics in Kuala Lumpur, Malaysia were individually interviewed. Data were analyzed using framework analysis. Symptoms of PND as explained by the women did not fully reflect medical diagnostic criteria, focusing instead on women’s emotional experiences and disturbances. Women’s causal explanations were different from one culture to another. For example, Malay and Chinese women felt traditional postnatal practices contributed to PND, whereas Indian women felt such practices actually served to promote maternal and child well-being. Whilst women have different experiences and explanations for PND they also shared many common experiences reflected in a set of physical, psychological and sociocultural causal factors.